Influence of videolaryngoscopy using McGrath Mac on the need for a helper to perform intubation during general anaesthesia: a multicentre randomised video-no-video trial. Issue 1 (3rd January 2022) - Belze, Olivier; Coppere, Zoé; Ouattara, Jonathan; Thion, Laurie-Anne; Paqueron, Xavier; Devys, Jean-Michel; Ma, Sabrina; Kennel, Titouan; Fischler, Marc; Le Guen, Morgan
Abstract : Objective: We hypothesised that videolaryngoscopy modifies practice of tracheal intubation. Design: Randomised single-blinded study (video and no-video groups). Setting: Three institutions: one academic, one non-profit and one profit. Participants: Patients >18 years, requiring orotracheal intubation, without predicted difficult intubation. Non-inclusion criterion was patients requiring a rapid-sequence intubation. 300 patients were included, 271 randomised, 256 analysed: 123 in the no-video and 133 in the video groups. Intervention: Tracheal intubation using a McGrath Mac videolaryngoscope, the sequence being video recorded. Primary and secondary outcome measures: The primary outcome was the proportion of intubations where assistance is necessary on request of the operator. Secondary outcomes included intraoperative variables (intubation difficulty scale and its components, percentage of glottic opening score, oesophageal Intubation, duration of intubation, removal of the screen cover in the no-video group, global evaluation of the ease of intubation, bispectral index, heart rate and blood pressure), intraoperative and postoperative complications (hoarseness or sore throat) and cooperation of the anaesthesiology team. Results: Requirement for assistance was not decreased in the Video group: 36.1% (95% CI 27.9 to 44.9) vs 45.5% (95% CI 36.5 to 54.7) in the no-video group, p=0.74; OR: 0.7 (95% CI 0.4 to 1.1) and absolute risk: 0.10 (95% CI −0.03 to 0.22). Intubation difficulty scale was similar in both groups (p=0.05). Percentage of glottic opening score was better in the Video group (median of 100 (95% CI (100 to 100) and 80 (95%CI (80 to 90) in the no-video group; p<0.001) as Cormack and Lehane grade (p=0001). Ease of intubation was considered better in the video group (p<0.001). Other secondary outcomes were similar between groups. Screen cover was removed in 7.3% (95% CI (2.7 to 11.9)) of the cases in the video group. No serious adverse event occurred. Communication and behaviour within the anaesthesia team were appropriate in all cases. Conclusion: In patients without predicted difficult intubation, videolaryngoscopy did not decrease the requirement for assistance to perform intubation. Trial registration number: NCT02926144; Results .